2000
DOI: 10.1001/archneur.57.7.1000
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Triphasic Perfusion Computed Tomography for Intravenous Thrombolysis With Tissue-Type Plasminogen Activator in Acute Ischemic Stroke

Abstract: Thrombolysis can be safely performed within 3 or 7 hours of stroke onset according to the extent of severe perfusion deficit on TPCT. A larger extent of moderate perfusion deficit on TPCT may predict early improvement after thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…A triphasic helical CT-based study previously demonstrated that the maximal enhancement in a nonoccluded artery was observed around 30 s after contrast material administration, followed by a decrease in contrast enhancement to half, then a plateau up to 60–180 s in ischemic stroke patients within 6 h after symptom onset [19]. Moreover, other studies using multiphasic contrast CT have shown that, compared with the arterial phase, the delayed phase showed a higher correlation with collateral circulation acquired by 4-vessel angiography [20,21]. Thus, contrast dye on CECT is at a more distal location compared with that in CTA-SI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A triphasic helical CT-based study previously demonstrated that the maximal enhancement in a nonoccluded artery was observed around 30 s after contrast material administration, followed by a decrease in contrast enhancement to half, then a plateau up to 60–180 s in ischemic stroke patients within 6 h after symptom onset [19]. Moreover, other studies using multiphasic contrast CT have shown that, compared with the arterial phase, the delayed phase showed a higher correlation with collateral circulation acquired by 4-vessel angiography [20,21]. Thus, contrast dye on CECT is at a more distal location compared with that in CTA-SI.…”
Section: Discussionmentioning
confidence: 99%
“…This logically explains the use of collateral circulation as a prognostic factor in acute ischemic stroke and, thus, the presence of collateral circulation predicts improved outcome in patients with MCA occlusive stroke [1,25,26]. In addition, reduced collateral circulation has been shown to increase the rate of mortality and hemorrhagic transformation [21,27,28]. Our study reaffirmed that patients with fair pial collateral circulation have a less severe symptomatic hemorrhage and a better prognosis than patients with bad pial collateral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients presenting less than 8 hours from symptom onset clearly do not have salvageable brain because of poor collaterals. 25 If good, rapid imaging capable of identifying ischemic penumbra were available to determine salvageable brain tissue (such as diffusion-weighted or perfusion-weighted MR imaging [26][27][28][29][30][31][32][33][34][35][36] or CT perfusion 37,38 ), intra-arterial interventions for ischemic stroke could be reduced by perhaps half because it would be possible to determine that infarction is complete before these patients are moved to an interventional suite. This would be of benefit to patients because it spares them futile, aggressive interventions.…”
Section: Who Needs Intra-arterial Ischemic Stroke Therapy?mentioning
confidence: 99%
“…In the field of acute stroke, MPCT has been used as a prediction tool for final infarct volume, infarct growth, subsequent brain edema, and clinical response after thrombolysis [3,6,7]. Previously, we reported that MPCT could also be used in assessing perfusion deficit and collateral circulation as reliably as DSA in a small number of patients [8].…”
Section: Discussionmentioning
confidence: 99%